La colaboración docente para la innovación institucional - Herrera Tapia, Joselyn Cristina (2023)
The current research work emphasizes the educational innovation importance and learning communities, since innovation is creating systems, what allow determining possible solutions and improvements in the significant results and learning extraction. So that, in the education, it ensures to generate changes in the society and which this is seen in a non-traditional way, where education does not depend, so much, what happens in the classroom, but rather that it appears as new ideas, for that reason, it is proposed to solve the following problem: How to generate educational innovation and the learning community's integration in the fourth grades from Cotopaxi Province Educational Unit, Pujilí Canton in the 2021-2022 school year? Considering this, it has been proposed the aim of promoting the educational innovation processes application, through the learning community's incorporation, in order to achieve improvements in the fourth grades pedagogical process. According to the research development, the methodology was based on the interpretive approach, since it allowed to understand the social context reality its own nature. In turn, it was used qualitative research, since it follows the stages: preparatory, informative analysis and it is descriptive, field and bibliographical. The applied method is the inductive one, the technique is the interview, and as an instrument the interview guide, which was directed to the teachers and the institution authority, the collected information allowed to show the real problems, what arise within the educative community. This project contributes to the proposal regarding the workshop on teacher collaboration skills and educational innovation, for the improvement of collaboration between teachers and the practice of collaborative strategies in the classroom. These aspects are aimed at generating changes in the professional and institutional field in this way the collaboration and integral participation of all for the strengthening of collaborative and investigative competences.